Aoridae - Myers, Alan A. (Zootaxa, 2009)
Five genera and 21 species of aorids are reported from the Great Barrier Reef, most of which belong to the genus Bemlos. One third of the species are new to science and half of them are currently known only from the Great Barrier Reef.